'His pen and ink are a powerful mirror'
1 online resource.
Keywords: “'His Pen and Ink are a Powerful Mirror' is a volume of collected essays in honor of Ross Brann, written by his students and friends on the occasion of his 70th birthday. The essays engage with a diverse range of Andalusi and Mediterranean literature, art, and history. Each essay begins from the organic hybridity of Andalusi literary and cultural history as its point of departure, introduce new texts, ideas, and objects into the disciplinary conversation or radically reassesses well-known ones, and represent the theoretical, methodological, and material impacts Brann has had and continues to have on the study of the literature and culture of Jews, Christians, and Muslims in al-Andalus. Contributors include: Ali Humayn Akhtar, Esperanza Alfonso, Peter Cole, Jonathan Decter, Elisabeth Hollender, Uriah Kfir, S.J. Pearce, F.E. Peters, Arturo Prats, Cynthia Robinson, Tova Rosen, Aurora Salvatierra, Raymond P. Scheindlin, Jessica Streit, Shawkat M. Toorawa, David Torollo“.